The effects of manufacturing tolerances and assembly force on the volumetric wear at the taper junction in modular total hip arthroplasty. Issue 13 (3rd October 2019) - Bitter, Thom; Khan, Imran; Marriott, Tim; Lovelady, Elaine; Verdonschot, Nico; Janssen, Dennis
Abstract: Fretting and corrosion at the taper-head interface in total hip arthroplasty has been reported as a potential cause of early failure of the implant system. The finite element (FE) method can be used to study the mechanics at the taper junction that are difficult to assess experimentally. Taper mismatch is one of the factors that can influence the performance of the taper junction. In this study we have assessed the effect of taper mismatch, in combination with assembly force on the volumetric wear. The study showed that higher assembly forces and smaller mismatches result in the least volumetric wear.